2015
DOI: 10.1038/pr.2015.81
|View full text |Cite
|
Sign up to set email alerts
|

Early decreased plasma levels of factor B and C5a are important biomarkers in children with Kawasaki disease

Abstract: Background:The mechanisms underpinning Kawasaki disease (KD) are incompletely understood. There is an unmet need for specific biomarkers for the early diagnosis of KD. Methods: Eighty-five KD patients suffering from acute-phase and subacute-phase KD, 40 healthy children, and 40 febrile children comprised the study cohort. An enzyme-linked immunosorbent assay was used to measure plasma levels of C1q, C1q-circulating immune complex (C1q-CIC), mannan-binding lectin-associated serine protease (MASP)-1, factor B, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…However, CD59 levels in plasma were found to be low at the early stage of KD (Song et al, 2016). In agreement with our results, plasma CD59 concentrations increased in acutephase KD patients compared with subacute-phase KD patients (Zou et al, 2015). Therefore, this inconsistent result requires further investigation.…”
Section: Discussionsupporting
confidence: 87%
“…However, CD59 levels in plasma were found to be low at the early stage of KD (Song et al, 2016). In agreement with our results, plasma CD59 concentrations increased in acutephase KD patients compared with subacute-phase KD patients (Zou et al, 2015). Therefore, this inconsistent result requires further investigation.…”
Section: Discussionsupporting
confidence: 87%
“…C-reactive protein (CRP) may further enhance the localised deposition of complement in the vessel wall, since gross elevation of CRP occurs in the acute phase of Kawasaki disease (and COVID-19) and this protein can mediate classical pathway activation of complement ( 26 , 27 ). A study in Kawasaki disease demonstrated that complement factor B (essential for alternative pathway activation) is likely to have a contributory effect ( 28 ). Other proteomic studies have identified strong associations of the complement and coagulation cascades with Kawasaki disease ( 29 ).…”
Section: Links Between Mis-c and Kawasaki Disease With The Complementmentioning
confidence: 99%